Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1046/j.1365-2990.1998.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Middle cerebral artery occlusion in the rat: consistent protocol for a model of stroke

Abstract: Variability in the effects of the intraluminal suture method of middle cerebral artery occlusion (MCAO) in the rat has been a common and disadvantageous finding. Therefore, we systematically investigated the effects of suture type and rat strain on outcome. First, the clinical and neuropathological effects of permanent MCAO with either an uncoated or a silicone-coated nylon suture were studied over 7 days in Sprague-Dawley rats (n = 36 for each type of suture). Outcome was less severe with the uncoated compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 34 publications
(58 reference statements)
7
68
1
2
Order By: Relevance
“…This might explain the considerable variability of results reported from different laboratories using similar MCAO techniques in rats (Coyle & Jokelainen 1982, Aspey et al 1998. In the present study, Sprague-Dawley and Wistar rats reacted differently to permanent and transient MCAO with respect to ischaemic lesion volume and oedema formation.…”
Section: Oedema Formationmentioning
confidence: 45%
See 1 more Smart Citation
“…This might explain the considerable variability of results reported from different laboratories using similar MCAO techniques in rats (Coyle & Jokelainen 1982, Aspey et al 1998. In the present study, Sprague-Dawley and Wistar rats reacted differently to permanent and transient MCAO with respect to ischaemic lesion volume and oedema formation.…”
Section: Oedema Formationmentioning
confidence: 45%
“…Several studies have reported differences in the extent of ischaemic lesion volumes among rat strains (Duverger & MacKenzie 1988, Markgraf et al 1993, Oliff et al 1995a,b, 1996, Sauter & Rudin 1995, Aspey et al 1998, Ren et al 2004. However, the effect of reperfusion on ischaemic lesion volume and oedema formation in consideration of rat strain differences has not been investigated systematically.…”
Section: Discussionmentioning
confidence: 99%
“…An image analysis system (NIH 1.61 software) was used to determine the infracted volume (MV), right hemisphere volume (RV), and left hemisphere volume (LV). To compensate for the effect of brain edema on the measured infarct volume in the ischemic hemisphere, the infarct volume in each mouse was corrected as described (Swanson et al, 1990;Aspey et al, 1998) with the following formula. Corrected infarct volume (%) ϭ [LV Ϫ (RV Ϫ MV)]/LV ϫ 100.…”
Section: Methodsmentioning
confidence: 99%
“…The intraluminal suture occlusion of the middle cerebral artery (MCAO) in rats is one of the most widely used models to study focal cerebral ischemia. However, considerable variability in the extent of final infarct size have been recurrent findings with this model 1,2 and compromised its potential in preclinical therapeutic assessments. This may be explained by a number of factors, including differences in anesthesia, in size and type of filament used, and modifications of the technique.…”
mentioning
confidence: 99%